The Influence of Paid, Owned, and Earned Social Media Content on the Customer Experience - Singh, Bhavina (Auckland University of Technology, 2023)
This study aims to understand how the customer experience is impacted in the context of so-cial media marketing. To do this, the three main types of social media content, paid, owned, and earned, are investigated in relation to the customer experience. This is researched in the context of Instagram to answer the research question, how does paid, owned, and brand-related content on Instagram impact the customer experience? This is a qualitative study which interviews ten participants who have made a purchase from Instagram within the last 6 months. The findings present three key themes: 1) perception of trust 2) product value 3) gender preferences. These themes are discussed in relation to the customer experience where paid and earned media impact the customer experience positively for female consumers and owned content impacts the customer experience positively for male consumers. It is also found that paid and earned media diminish the exclusivity associated with owning high-value products. The findings of this research imply that factors such as the value of the product and the gender of the target audience for the product should be considered when using paid, owned, and earned social media content to create positive customer experiences.
Keywords: Social Media; Customer Experience; Customer Perception; Customer Journey; Paid Media; Owned Media; Earned Media